43 Raised Natriuretic Peptides are not Exclusively Indicative of Heart Failure: A Service Review of a Diagnostic Heart Failure Clinic. (31st May 2014) - Fent, Graham; Hall, Ian; Watt, Victoria; O'Toole, Lawrence; Al-Mohammad, Abdallah
Abstract : Introduction: An incident heart failure (HF) diagnostic clinic implementing the NICE guidelines was established at Sheffield Teaching Hospitals in 2012. General Practitioners (GPs) refer patients with suspected HF and NT-pro BNP >400 pg/ml. The patients undergo ECG and echocardiography on the day of the assessment by a Consultant Cardiologist, who gives a detailed diagnosis and management plan. Methods: Records of all the non-HF patients seen in the clinic in the first year to April 2013 were reviewed to assess the recorded causes of their presentation and their prevalence.We excluded any patients accessing the clinic without NTproBNP level. Results: A total of 697 were seen, of whom 557 (79.9%) had HF (HFPEF, HF-LVSD, HF secondary to valvular heart disease or secondary to pulmonary hypertension). Atrial fibrillation/flutter was present in 276 patients (39.6% of all the patients). There were 140 (20.1%) with no HF. Of the patients with no HF, 33 were asymptomatic and thus inappropriately referred. Eleven patients had angina. In the remaining 96 patients with no HF, 71 (74%) were given firm diagnoses including: Atrial Fibrillation/Flutter (30), Chronic Obstructive Pulmonary Disease (23), Cancer (5), multifactorial cause (3), Pulmonary Fibrosis (3), Anaemia (2), Nephrotic Syndrome (1), Obstructive Sleep Apnoea (1), Pneumonia (1), Radiation Pneumonitis (1) and Sarcoidosis (1). In the remaining 25, no firm diagnosis was made but advice was given to the GPs on further assessment. Therefore of all the patients seen in the clinic, 96.4% were given a diagnostic explanation. Conclusions: This review confirms the effectiveness of a 'one-stop' Consultant-led HF diagnostic service, and highlights the multitude of causes for raised NTproBNP beyond HF.